Salvianolic Acid B Attenuates Experimental Pulmonary Fibrosis through Inhibition of the TGF-β Signaling Pathway - Liu, Qingmei (Sci Rep, 2016)
Pulmonary fibrosis is a progressive and fatal disorder. In our previous study, we found that the Yiqihuoxue formula (YQHX), a prescription of Traditional Chinese Medicine, had a curative effect on scleroderma, a typical fibrotic disease. The aim of this study was to determine the key ingredient mediating the therapeutic effects of YQHX and to examine its effect on pulmonary fibrosis, including its mechanism. Luciferase reporter assays showed that the most important anti-fibrotic component of the YQHX was Salviae miltiorrhiza (SM). Experiments performed using a bleomycin-instilled mouse model of pulmonary fibrosis showed that Salvianolic acid B (SAB), the major ingredient of SM, had strong anti-inflammatory and anti-fibrotic effects through its inhibition of inflammatory cell infiltration, alveolar structure disruption, and collagen deposition. Furthermore, SAB suppressed TGF-β-induced myofibroblastic differentiation of MRC-5 fibroblasts and TGF-β-mediated epithelial-to-mesenchymal transition of A549 cells by inhibiting both Smad-dependent signaling and the Smad-independent MAPK pathway. Taken together, our results suggest that SM is the key anti-fibrotic component of the YQHX and that SAB, the major ingredient of SM, alleviates experimental pulmonary fibrosis both in vivo and in vitro by inhibiting the TGF-β signaling pathway. Together, these results suggest that SAB potently inhibits pulmonary fibrosis.